Guided Resonance in Photonic Crystals - Du, Pei (My University, 2014)
The objective of this thesis research is to analyze the guided resonances in photonic crystal slabs. It introduces the different kinds of photonic crystals and focuses on photonic crystal slabs consisting of a square lattice of air holes. The guided resonances are created by the coupling between the guided modes above the light line and radiation modes. Specifically, we calculate the transmission spectra of the guided resonances. Our work is mainly based on four parts. Firstly, we introduce the background of photonic crystals and then we discuss the properties of different kinds of photonic crystals. Next, we briefly discuss the software that we use to plot transmission spectra. Finally, we focus on band structure of guided resonances in photonic crystal slab, use time domain analysis including computational methods and line shape analysis by introducing a general and intuitive mode, and summarize the result. The research in the thesis show the guided resonances are strongly confined in the dielectric slabs and coupled to radiation modes at the same time. Through the transmission spectra, we can see that it is modified from the result of uniform photonic slab. The new spectra contain some sharp resonant peaks and the line shape shows complex asymmetries which comes from the interference between direct and indirect pathways.
Keywords: Guided Resonances; Photonic Crystal Slabs; Transmission Spectra; Time Domain Analysis